O BALANÇO DE NUTRIENTES EM PASTAGENS PARA GADO LEITEIRO EM IJUÍ - Weber, Adriano J.; Fernandes, Sandra B. V.; Berto, Jorge L.; Uhde, Leonir T.; Garcia, Dagmar C.; Quadros, Valmir J. d. (Salão do Conhecimento, 2013)
Resumo